2022
DOI: 10.1038/s41598-021-04302-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of peripheral blood mononuclear cells from juvenile dermatomyositis patients show elevated inflammation even when clinically inactive

Abstract: In juvenile dermatomyositis (JDM), the most common pediatric inflammatory myopathy, weakness is accompanied by a characteristic rash that often becomes chronic and is associated with vascular damage. We hoped to understand the molecular underpinnings of JDM, particularly when untreated, which would facilitate the identification of novel mechanisms and clinical targets that might disrupt disease progression. We studied the RNA-Seq data from untreated JDM peripheral blood mononuclear cells (PBMCs; n = 11), PBMCs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
(65 reference statements)
6
19
0
Order By: Relevance
“…As previously reported (8,9), juvenile DM patients had a markedly distinctive transcriptional signature. Juvenile DM patients had 1,426 differentially expressed genes compared with healthy controls ( P ≤ 0.05).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…As previously reported (8,9), juvenile DM patients had a markedly distinctive transcriptional signature. Juvenile DM patients had 1,426 differentially expressed genes compared with healthy controls ( P ≤ 0.05).…”
Section: Resultssupporting
confidence: 81%
“…Thus, whether Th2 cells play a pathogenic role in juvenile DM or they expand in response to muscle damage remains to be addressed. Importantly, expansion of CXCR5 low/− CM B cells correlated with increased ISG transcriptional expression, a known feature of juvenile DM (8,9); therefore we tried to dissect this further. The type I ISG signature has been previously found to correlate with measures of global and muscle DA and is thought to drive pathology (8,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to utilize RNAseq on multiple sorted immune cell subsets to compare differential upregulated and downregulated gene expression in NK, B, and T cells from new-onset JDM patients and healthy pediatric controls. The only four prior published RNAseq studies in JDM that we are aware of include a study of total PBMCs from JDM patients ( 55 ), plasma exomes from JDM patients ( 56 ), study of B cells of JDM patients ( 8 ), and a comparison of JDM treatment responders vs non-responders ( 57 ). While these studies have mainly explored JDM PBMC transcription as a whole (with the exception of the study focused on B cells), we chose to compare highly enriched sorted lymphocyte subsets to gain further insight into JDM pathogenesis by delineating the role of each of these subsets at the transcript level.…”
Section: Discussionmentioning
confidence: 99%
“…We found that some of the significantly enriched GO terms have been mentioned in the context of other infectious diseases. In the microarray example, we selected the biological process GO:0002483 which was also found enriched in a study on juvenile dermatomyositis [ 34 ], which is supposed to be caused by viruses and can involve inflammation of the lung. The cellular component of phagocytic vesicles (GO:0045335) was also mentioned in the context of SARS-CoV-2 infection and pulmonary fibrosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%